Chronic conditions among children, adolescents, and young adults in acute care settings. (30th September 2020) - Sentell, T; Choi, S Y; Ching, L; Quensell, M; Keliikoa, L B; Corriveau, E; Pirkle, C
Abstract: Background: Despite a growing prevalence of chronic disease risk factors, such as obesity, among young people in the United States and other countries, little is known about actual disease prevalence in this population. Almost nothing is known about this topic in many racial/ethnic groups that are rapidly growing in the United States, including Native Hawaiians, Other Pacific Islanders, and Filipinos. Yet these understudied groups are at high risk. The study goal was to determine the statewide prevalence of chronic disease in acute care for those aged 5-29 years, including Native Hawaiians, Filipinos, and Pacific Islanders. Methods: Using Hawai'i statewide inpatient and emergency department (ED) data across all payers from 2015-2016, we considered the presence of at least one of five target chronic conditions (asthma, hypertension, chronic kidney disease, diabetes, stroke) from 13, 514 inpatient stays by 9, 467 unique individuals and 228, 548 ED visits by 127, 854 individuals. Results: Twenty-eight percent of youth who were hospitalized and 12% with an ED visit had at least one chronic condition. In both inpatient and ED settings, race/ethnicity, age group, and payer varied significantly when comparing those with a chronic condition to those without a chronic condition. Notably, those with a chronic condition were disproportionately Native Hawaiian, Filipino, and Pacific Islander; 32.3% percent of those with an inpatient chronic condition and 34.9% of those with an ED chronic condition were Native Hawaiian. Conclusions: Chronic diseases, including those more often seen in adulthood, are prevalent in young people in acute care settings in the state of Hawai'i with notable disparities. This data can help justify, guide, and support programs urgently needed to address these changing epidemiological trends, which may be of particular interest for Medicaid. Key messages: We show that chronic conditions are prevalent in young people in acute care settings in the state of Hawai'i with notable disparities. This can help justify, guide, and support programs to address these troubling epidemiological trends.